PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN KETERAMPILAN MEMBACA AL- QUR’AN MENGGUNAKAN METODE IQRO’ UNTUK SISWA TUNARUNGU DI SLB- B JATI WIYATA DHARMA TUBAN - Nadia Faradibaa; Abdul Jalil; Imam Safi’i (VICRATINA, 2022)
Education is a very important thing for human life. Likewise for the Indonesian people. Education ranks most important. Islamic religious educationhas an important role to create religious and noble human beings. In learning the religious of Islam, muslims are required to study the Qur’an as one of the guidelines for the people. Al- Qur’an is kalamullah which contains the sorce of Islamic teachings and as a guide and guide for human life. The learning method to improve reading skill of the Qur’an for deaf students at SMPLB level at SLB- B JatiWiyata Dharma TubanisIqro’ method. Besides being applied to regular children, the Iqro’ method can also be appliedto deaf students. This study reviews the learning processto improve reading skills of the Qur’an for deaf students using the Iqro’ method at SLB- B JatiWiyata Dharma Tuban. The techniques used in learning the skills of reading the Qur’an using the Iqro’ method are the pre- perdata techniques, ideovisual reading, reflection exercises and writing exercises. And supported by the learning media used are mirrors and letter cards. This study uses a qualitative method where data collection uses observation, interview and documentation techniques. The analysis techniques used in this study consists of four stages: 1) data collection, 2) datacondensation, 3) datadisplay,4) conclusiondrawing/verivication